Trend changes of the geomagnetic field at the observatory “Argentine Island”: effect in Sq-variations - Maksimenko, O. I.; Bakhmutov, V. G.; Kilifarska, N.A.; Shenderovska, O. Ya. (Ukrainian Antarctic Journal, 2013)
Trends of the geomagnetic Sq-variation daily amplitudes on the observatory "Akademic Vernadsky" were obtained with the weakening of the end of the interval 1958 to 2010. The daily Sq-variation amplitudes have trends with the same magnitude of 0.06 nT / year, but different signs for horizontal. SqH and vertical. SqZ components of the geomagnetic variations that are defined by a decrease of 8.6% and 11.3% increase in. The ionospheric conductivity is increasing on 16 % in 50 years. It was found that the secular variations of the magnetic field gives 10% contribution to the trend SqH-geomagnetic variations in the summer, and the effect of Ap index and <span style="background-color: #ffffff; color: #000000; font-family: " noto sans",arial,helvetica,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">СО2 anomalies failed to reveal to obs. AIA with the negative trend of the magnetic field in the last century.